Analysis of the Actual Water Discharge Requirements for Existing Agricultural Land in D.I Cipari Makmur - HJ, Aripin Noor; Tukimun, Tukimun; Nur, Alpian (Elektriese: Jurnal Sains dan Teknologi Elektro, 2024)
Irrigation systems play a crucial role in supporting agricultural productivity, especially in regions dependent on water availability. The Cipari Makmur Irrigation Area (D.I. Cipari Makmur) is an agricultural region facing challenges related to the imbalance between water supply and demand due to changes in cropping patterns and hydrological conditions. This study aims to analyze the actual water discharge requirements to ensure efficient and sustainable distribution. The research methodology includes a hydrological analysis based on rainfall data from 2014–2023 and an evaluation of the balance between water availability and demand using a water balance approach. The results indicate a rainfall pattern with two main peaks: March–June (175–245 mm) and September–December (160–230 mm), with a deficit period occurring in July–August (90–135 mm). The highest water availability is recorded in February (1.05–1.09 m³/sec) and October (1.10–1.09 m³/sec), whereas a critical deficit is observed from June to August, with availability approaching 0.00 m³/sec. This imbalance highlights the need for adaptive water resource management strategies, such as the construction of reservoirs or retention basins to store surplus water and the optimization of irrigation system efficiency. These findings can serve as a basis for decision-making to enhance agricultural water resilience in DI Cipari Makmur. Further research could explore the impact of climate change on water availability and develop more effective mitigation strategies.